Lasater clinical judgment rubric in nursing education: a Turkish validity and reliability study - Esra Sezer; Hilal Yıldız Çelik; Ükke Karabacak; Kathie Lasater (BMC Nursing)
Abstract Introduction Gaining clinical judgment competence among student nurses is a significant outcome of nursing education. In this education process, an assessment tool based on observable behaviors is needed for evaluating students’ clinical judgment skills. Objective This study aimed to evaluate the validity and reliability of the Turkish version of the Lasater Clinical Judgment Rubric, which assesses student nurses’ stages of clinical judgment competency in simulation-based education. Method This study was conducted using a cross-sectional methodological design between April and August 2024. For the cultural adaptation and psychometric evaluation of the rubric, simulation videos of 3rd and 4th-year nursing students from a foundation university were used. The language validity of the rubric was performed according to the 10-step translation and cultural adaptation guide of the International Society for Pharmacoeconomics and Outcomes Research; expert opinions were obtained for content validity. The final version of the rubric comprises four stages of the Tanner Model of Clinical Judgment (noticing, interpreting, responding, and reflecting) and 11 dimensions. Four levels of achievement describe the development of each of the 11 dimensions. Sixty-four scenario records of the simulation-based education of 4th -year students in the nursing undergraduate program of a foundation university were examined, and the students were evaluated by two independent observers using the Turkish version of the rubric. The construct validity of the scale was examined using confirmatory factor analysis, and reliability was measured using Cronbach’s alpha coefficient. Interobserver agreement was analyzed using the kappa and intraclass correlation coefficients. Moreover, the discrimination of the rubric was evaluated using an independent samples t-test between the lower and upper 27% groups. Results Confirmatory factor analysis revealed that the scale formed a four-factor structure of noticing, interpreting, responding, and reflecting in accordance with the original rubric. Furthermore, confirmatory factor analysis showed that the four-factor structure model had an acceptable and generally good fit and was statistically significant and valid. The fit indices for the model were calculated as χ2/df = 1.70, root mean square error of approximation = 0.06, comparative fit index = 0.94, and root mean square residual = 0.03. Kappa values ranged between 0.72 and 0.92, indicating a significant fit for all the items. The intraclass correlation coefficient values ranged between 0.70 and 0.90 and were statistically significant for all the items. The Cronbach’s alpha value of the rubric was 0.91 and ranged between 0.80 and 0.84 in its subdimensions. Conclusion Therefore, the Turkish version of the rubric is a valid and reliable tool for evaluating student nurses’ clinical judgment competency in simulation-based training.